Medical comorbidities as predictors of COVID-19 short-term mortality: A historical cohort study in Indonesia - Rizaldy Taslim Pinzon; Vanessa Veronica (Tzu Chi Medical Journal)
Objectives: In this study, we aimed to evaluate the relation of comorbidities to coronavirus disease 2019 (COVID-19) short-term mortality. Materials and Methods: This was a single-center observational study with a historical cohort method at Bethesda Hospital Yogyakarta, Indonesia. COVID-19 diagnosis was made using reverse transcriptase–polymerase chain reaction on nasopharyngeal swabs. Patient data were obtained from digital medical records and used for Charlson Comorbidity Index assessments. Inhospital mortality was monitored throughout their hospital stay. Results: This study enrolled 333 patients. According to the total number of comorbidities in Charlson, 11.7% (n = 39) of patients had no comorbidities; 30.9% (n = 103) of patients had one comorbidity; 20.1% (n = 67) of patients had two comorbidities; and 37.2% (n = 124) of patients had more than three comorbidities. In multivariate analysis, these variables were significantly related to short-term mortality in COVID-19 patients: older age (odds ratio [OR] per year: 1.64; 95% confidence interval [CI]: 1.23–2.19; P 0.001), myocardial infarction (OR: 3.57; 95% CI: 1.49–8.56; P: 0.004), diabetes mellitus (OR: 2.41; 95 CI: 1.17–4.97; P: 0.017), renal disease (OR: 5.18; 95% CI: 2.07–12.97; P < 0.001), and longer duration of stay (OR: 1.20; 95% CI: 1.08–1.32; P < 0.001). Conclusion: This study revealed multiple short-term mortality predictors in COVID-19 patients. The coexistence of cardiovascular disease, diabetes, and renal problem is a significant predictor of short-term mortality in COVID-19 patients.